Initiation of use of alcohol, cigarettes, marijuana, cocaine, and other substances in US birth cohorts since 1919. - Johnson, R A (1998)
OBJECTIVES: This study examined recent trends in initiation of psychoactive drug use. METHODS: Data from the 1991 through 1993 National Household Surveys on Drug Abuse were used to compare the percentages of US cohorts born from 1919 through 1975 who began using drugs before the ages of 15, 21, and 35. RESULTS: Initiation of cigarette smoking by males peaked in the 1941-1945 cohort, then declined steadily. For females, early smoking initiation rose through the 1951-1955 cohort and then stabilized. Initiation of alcohol use was less common than smoking for pre1950 cohorts but increased steadily, approaching cigarette use for cohorts born in the early 1970s. Only 2% of teenagers born in 1930-1940 tried marijuana; half the teenagers born in 1956-1965 did so. The percentage initiating marijuana use declined in the 1980s, more so among young adults than among teenagers. The use of cocaine and other illicit drugs echoed the rise of marijuana use but peaked later and showed less evidence of subsequent decline. Sex differences declined over time for every drug. CONCLUSIONS: Cohorts born since World War II have had much higher rates of illicit drug use initiation, but trends have varied by drug type, possibly reflecting changes in relative prices.